Integrating agency and resource dependency theories: the moderating effect of board size on the relationship between dividends and firm value in Malaysia - Mohd Ashari Bakri; Nurjeehan Ayub; Hanefa Muchlis Gazali (ResearchGate, 2024)
Purpose This paper aims to examine the moderating efects of board size on the relationship between dividends and frm value in Malaysian settings. The theoretical foundations of this research were the integration between agency and resources dependency theories. Design/methodology/approach Panel data are extracted from DataStream and the annual report for the period of 2012 to 2021, and pooled OLS, random efects, and fxed efects analyses were employed to examine the relationship. Breusch–Pagan Lagrange multiplier (LM) test and the Hausman test used to determine the most appropriate between these three analyses (OLS, random efects, and fxed efects). The results are valid even after calculating the robust standard error to mitigate the potential heteroskedasticity and serial correlation. Findings The empirical results show that board size positively moderates the relationship between dividends and frm value in all the models tested. The results indicate that a larger board of size can minimize the agency problem (agency theory) because a larger board size can more efectively monitor and control management’s opportunistic behavior due to more set of skilled and talented individuals included in the boardroom (resources dependency theory). Additionally, efective monitoring can also lead to the increase in dividend payout to maintain a good reputation among investors and simultaneously increase frm value. Practical implication This study contributes to helping the regulators and industry players in Malaysia to improve existing guidelines for determining dividend and board size to increase frm value. The fndings may also provide inputs to the policymakers in recommending the optimum dividend and board size that resulting an increase in valuation. Originality/value By incorporating agency and resources dependency theory, authors investigate the moderating efect of board size on dividend and frm value relationships in Malaysian markets